Dental Metric on The Late Holocene to Current Era Population from The Lowland Part of Indonesian-Papua - Marlin Tolla; Hirofumi Matsumura; Dominik Bonatz; Kathrin Nägele; Cosimo Posth (Badan Riset dan Inovasi Nasional, 2023)
In an attempt to understand human history in this world, the researchers have applied several methods to identify the group of populations based on the teeth trait characteristic. However, the lack of knowledge about human diversity from several regions in this world derived from the osteological study from archaeological context has limited the understanding of human history in many societies including the populations that occupied the lowland part of Indonesian-Papua. For this, the aim of this study is to reconstruct the population history by employing the dental metric measurement on the 304 samples from the archaeological sites in the lowland parts of Indonesian- Papua which are classified into two different groups, Late Holocene and Current Era. The multivariate statistics analysis was applied to compare the results from the Lowland Indonesian- Papua samples with 17 groups of the population included in this study. The results from the statistics measurement were further used to reconstruct and visualize the phylogenic tree by employing The Neighbor-Joining method and UPGMA algorithm. The result from this clustering group presents the data about East Asian affinities for the Late Holocene and Australo Melanesian for the. Current Era group.